Congestion Games with Malicious Players - Babaioff, Moshe; Kleinberg, Robert; Papadimitriou, Christos H. (Games and Economic Behavior (GEB), 2009)
We study the equilibria of non-atomic congestion games in which there are two types of players: rational players, who seek to minimize their own delay, and malicious players, who seek to maximize the average delay experienced by the rational players. We study the existence of pure and mixed Nash equilibria for these games, and we seek to quantify the impact of the malicious players on the equilibrium. One counterintuitive phenomenon which we demonstrate is the “windfall of malice”: paradoxically, when a myopically malicious player gains control of a fraction of the ﬂow, the new equilibrium may be more favorable for the remaining rational players than the previous equilibrium.